Study on effect of colloidal Nano silica blended con-crete under compression - Reddy, Avuthu Narender; Meena, T (International Journal of Engineering and Technology, 2018)
Ternary Blended Concrete (TBC) with Nano-Silica (NS) is receiving special attention because of its ability to improve the performance of concrete as compared with the control concrete. The present investigation deals about the behavior of TBC produced, using Fly Ash (FA) and Alccofine (ALC) as a partial replacement for cement along with four different types of colloidal NS (CemSynXLP, CemSynXTX, CemSynXFX, CemSynXTXla) as additives. The compressive strength of M30 grade of TBC was tested after 7, 14 and 28 days of curing. From the study, it has been found that the TBC mix with 25% replacement for cement (FA at 15% and ALC at 10%) and with addition of 1% CemSynXTXla type of NS as an additive has achieved higher strength than all other types of TBC mixes.